TEORI PEMBELAJARAN KONSTRUKTIVISTIK DALAM MENINGKATKAN HASIL BELAJAR SOSIOLOGI DI SMA - Fitri Anjani (SocioEdu: Sociological Education, 2020)
The purpose of this study is to find out if the theory of constructive study can improve the outcome of the learning sociology. The method used qualitative which analyses several journals of constructive theory by reviewing the journals. This is one way of analysis and synthesized critical and deep out of that journal. The data was analysed with qualitative teachniques among reviewing journal, reading, studying, coding, writing and visualization. The results of the several journal analysis show that constructivist learning theory can improve learning outcomes and student activity, and students not only receive learning material from the teacher but students are also able to understand, transfer and develop the knowledge they have. The constructivist learning theory can also improve student learning outcome, such it is obtained from constructing students’ knowledge by solving problems in the learning process that are done independently or in groups.